Interactional strategies for progressing through quizzes in dementia settings. (August 2020) - Webb, Joseph; Lindholm, Camilla; Williams, Val
People with early-to-mid stage dementia frequently attend groups that provide opportunities for socialising and engaging in group activities, such as quizzes. This article uses conversation analysis to investigate the interactional strategies that the staff use to initiate and keep these quizzes 'on track', and what they orient to as impediments and facilitators of quiz progression. Specifically, we outline how staff deal with incorrect or 'non-answers', and what happens when players have their own goals or 'projects' that do not align with staff members' orientations to the overarching activity completion. We reflect on the tensions that arise between doing interactional work to progress through the quiz, and how that goal can conflict with attending to the needs or wishes expressed by the person living with dementia, potentially resulting in threats to the 'face' of the quiz players. Data are taken from a corpus of 10 quizzes recorded in 4 different group settings in England.